Sexual harassment of working women between criminalization and punishment - Mahrouk, Karima (Journal of Human Sciences, 2020)
Many specialists in the field of psychiatry and Shari’a confirm that sexual harassment is one of the most secret crimes in Algeria, which kills daily working women who find themselves unable to prove the harassment they often end up having devastating psychological effects that the forensic doctor can not prove , Which contributes to the spread of this type of crimes that need new medical and legal mechanisms to prove them. This prompted the Algerian legislature to devote penal protection to women from sexual harassment in its amendment to the Penal Code under article 341 bis of Law 04/15, which includes the Penal Code. The legislator has thus removed this crime from the political, social and legal circle to the prohibited prohibition and legal interdiction The penalty.